A closer look at determinants of organizational capability to innovate (OCI): A dynamic capabilities perspective. Issue 3 (20th March 2020) - Montreuil, Véra-Line; Lauzier, Martin; Gagnon, Stéphane
Abstract : Purpose: The purpose of this paper is to provide a portrait of the main managerial and organizational determinants of organizational capability to innovate (OCI). Despite its importance, research on the subject seems limited, and little attempt has been made, over the years, to offer an in-depth and simultaneous analysis of these particular determinants, as well as an exploration of the underlying and complex mechanisms explaining their relationships to OCI. Design/methodology/approach: A systematic review of articles published between 1991 and 2018 was conducted in ProQuest (ABI/INFORM Collection) and Scopus databases. A total of 64 articles were selected and analysed through the use of a coding grid. Findings: Results highlight five key OCI determinants, namely: leadership, support, communication, culture, and learning. By using the dynamic capabilities theory (DCT) as a framework, this research suggests ways to better understand the dynamic action of these determinants as well as their contributions to OCI. Findings also suggest that OCI should be defined at the confluence of three perspectives (human, procedural and environmental aspects) to embrace the multiple facets of this complex construct. Proposals for future research are provided on how OCI can be better examined. Originality/value: This research helps to understand the five core determinants through an integrated and holistic view and represents the first attempt to systematically analyse the scientific literature on OCI through the DCT lens.